2018
DOI: 10.1007/s00246-018-1811-1
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Cardiac Troponins: Could They Be New Biomarkers in Pediatric Pulmonary Hypertension Due to Congenital Heart Disease?

Abstract: To analyze the role of sensitive cardiac troponin I (scTnI) and high-sensitive troponin T (hscTnT) in the determination of myocardial injury caused by volume and pressure load due to pulmonary hypertension (PH) and to investigate if these markers may be useful in the management of PH in childhood. Twenty-eight patients with congenital heart disease (CHD) with left to right shunt and PH, 29 patients with CHD with left to right shunt but without PH, and 18 healthy children, in total 75 individuals, were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
4
5
0
Order By: Relevance
“…In the present study, hs-cTnT levels were statistically significantly higher in the PH group compared with the healthy control cases and the non-PH group. This is in agreement with Kayali et al [13], who reported that both hs-cTnI and hs-cTnT levels were statistically significantly higher in the PH group compared with the healthy control cases and CHD cases with normal pulmonary artery pressure (the non-PH group).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, hs-cTnT levels were statistically significantly higher in the PH group compared with the healthy control cases and the non-PH group. This is in agreement with Kayali et al [13], who reported that both hs-cTnI and hs-cTnT levels were statistically significantly higher in the PH group compared with the healthy control cases and CHD cases with normal pulmonary artery pressure (the non-PH group).…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed that at hs-cTnT cut off value of [>85.2 pg/ml]; the sensitivity of hs-cTnT was (70%), specificity was (95%), Positive Predictive Value (PPV) was (93.3%), Negative Predictive Value (NPV) was (76%), and accuracy was (88.4%). This in agreement with Kayali [13], who reported that the sensitivity and specificity of serum hs-cTnT levels in the prediction of pulmonary hypertension were determined as 78% and 80%, respectively. Besides; in patients with CHD having higher serum hs-cTnI and hs-cTnT levels, there was an increased probability of the presence of pulmonary hypertension.…”
Section: Discussionsupporting
confidence: 91%
“…Our results also showed significantly higher serum hsTnT levels in patients with PH compared to those without PH, as also noted by Kayali et al [23]. Ventricular hypertrophy in response to higher ventricular pressure limits myocardial perfusion and increases oxygen demand, leading to a higher risk of myocardial injury and increased troponins [24].…”
Section: Discussionsupporting
confidence: 90%
“…In CHD patients, PAH triggers myocardial damage independently from increased volume or pressure load and resistance and disrupts perfusion due to increased ventricular wall strain and myocardial oxygen requirement. Serum hscTnT levels are useful determinants for identifying PAH-related damage [38].…”
Section: Role Of Hs-ctnt In the Prognosis Of The Patients With Pulmonmentioning
confidence: 99%